A história universal das nações de Giambattista Vico e a barbárie regressada na idade dos direitos humanos - Rodrigues, André Quintela Alves (2024)
At this time the objective is to break the paradigm of temporality based on the idea of constant and linear progress of humanity, subject to the fundamentalist treatment dispensed for nations peripheral to human directions, in terms of compatibility with local culture, denouncing the excess of internationalization in the current paradigm incorporation of International Human Rights Treaties. For this reason, dissociation is used within the ontogenetic and phylogenetic development of humanity, starting from the concrete natural direction of Giambattista Vico, following the archetypal idealization of the divine direction (theocracy), the heroic direction (aristocracy), the direction of humanity (humanist-theocêntrico). Next step, present the idea of human directions, as an archetypal repetition of the conflict of orders and of domination among nations. This last human story, Viquiana's historical perception, is projected into the historical context of the modern and contemporary world, as well as past juridical-arquetypical repetitions, a specific optic, embracing the historical events of imperialism in centuries-old nations rais no sec. XIX, the total war between powers in the first half of the XX century, the process of elaboration and drafting of the Universal Declaration of Human Rights of 1948, the reorganization and polarization of the world order after war and the war against terrorism. The intervention of central countries for the resolution of international conflicts under the justification of violation of human rights is exposed as a repetition of the argument of domination between central nations on the periphery and of regression from humanity to barbarism. Starting from a historicist anthropology, he defends the insustainability of the universal character of human directions, its artificiality, the insufficiency of openness and generality of its normative language for the effectiveness of effective multiculturalism, deviating from its relation to reality and vision of the world from peripheral nations . Defends, in particular, the necessity of regionalization of human rights, through prior constitutional filtering and/or legal regulation of International Trade, the maintenance of system centralization by CR/88, as the National Identity Policy Card, for the national condition the peripheral is not emancipated in terms of social demands, education and concern for the substantive ethics of civil society. Proposes a redirection from legal hermenêutica to achieve national culture.